Dynamic Outside Options and Optimal Negotiation Strategies - McClellan, Andrew (American Economic Review, 2024)
We study the design of negotiation strategies when a principal and agent must decide how to split a pie while the agent's outside option changes over time. The principal's optimal strategy under commitment demonstrates a new, but intuitive, set of negotiation dynamics. When the agent is tempted to leave, the principal gradually promises a larger share (decreasing demands) and more time to explore the outside option (decreasing pressure), illustrating a complementarity between these two tools. Although the principal's expected utility is decreasing in the outside option, his expected utility and demands are increasing in the outside option's drift and volatility. (JEL D63, D82, D86)